Suriname : Report on the Observance of Standards and Codes - Accounting and Auditing - World Bank (Washington, DC, 2012)
This report provides an assessment of the corporate sector accounting, financial reporting, and auditing practices in Suriname, with the aim of assisting the Government of Suriname's efforts to strengthen private sector accounting and auditing practices and enhance financial transparency in the corporate sector, so as to support the Government's objective of private sector-led growth and deepened integration with the international economy. This ROSC A&A aims to support the government's objectives of improving the investment climate and fostering private sector growth, in particular through: (a) designing a solid legal and regulatory framework governing the accounting and audit profession in Suriname, (b) improving the technical skills of accounting and audit practitioners, and (c) enhancing the institutional capacity of the country's accounting professional body and educational institutions. The ROSC A&A focuses on the institutional framework regulating accounting and auditing practices, and the comparability of national accounting and auditing practices with international standards and best practice, using International Financial Reporting Standards (IFRS) and International Standards on Auditing (ISA) as benchmarks. It evaluates the effectiveness of enforcement mechanisms for ensuring compliance with applicable standards and codes.